2011
DOI: 10.1128/ec.00205-10
|View full text |Cite
|
Sign up to set email alerts
|

The C-Module-Binding Factor Supports Amplification of TRE5-A Retrotransposons in the Dictyostelium discoideum Genome

Abstract: Retrotransposable elements are molecular parasites that have invaded the genomes of virtually all organisms. Although retrotransposons encode essential proteins to mediate their amplification, they also require assistance by host cell-encoded machineries that perform functions such as DNA transcription and repair. The retrotransposon TRE5-A of the social amoeba Dictyostelium discoideum generates a notable amount of both sense and antisense RNAs, which are generated from element-internal promoters, located in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 33 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…In cells of the CbfA mutant JH.D, both plus-and minus-strand RNA from the retrotransposon TRE5-A is diminished and the mobility of the endogenous retrotransposon population is drastically reduced (13). Thus, CbfA is a positive regulator of TRE5-A amplification.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In cells of the CbfA mutant JH.D, both plus-and minus-strand RNA from the retrotransposon TRE5-A is diminished and the mobility of the endogenous retrotransposon population is drastically reduced (13). Thus, CbfA is a positive regulator of TRE5-A amplification.…”
mentioning
confidence: 88%
“…Expression and retrotransposition of TRE5-A can be restored in JH.D cells by the ectopic expression of the fulllength CbfA protein. Interestingly, the expression of the isolated carboxy-terminal domain (CTD) of CbfA in the mutant cells was sufficient for complete restoration of the TRE5-A transcript levels, even though TRE5-A retrotransposition was unaffected (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely for the purpose of suppressing transposition, the organism has evolved a sophisticated RNAi machinery that includes, for example, three RNA-dependent RNA polymerases (RdRPs), two Dicer-like proteins, and five Argonaute-like proteins [ 13 17 ]. Intriguingly, the non-long terminal repeat retrotransposon TRE5-A has established a fairly high amplification rate in growing D. discoideum cells [ 18 , 19 ] despite the constitutive production of minus-strand RNA from an element-internal promoter [ 20 , 21 ]. Thus, how TRE5-A manipulates the cellular RNAi machinery to maintain its remarkable retrotransposition activity is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analyses revealed that CbfA has general gene regulatory functions in D. discoideum cells [ 28 ], making this protein an attractive candidate as a host protein that could limit TRE5-A expression and retrotransposition by elevating TRE5-A-derived minus-strand RNA. Interestingly, we observed that both plus- and minus-strand RNA of TRE5-A were reduced concurrently in the CbfA mutant by more than 90 %, and this reduction of transcript levels was accompanied by a sharp drop in TRE5-A’s retrotransposition activity in vivo [ 21 ]. Remarkably, the promoter activity of neither the A-module (TRE5-A’s plus-strand RNA promoter) nor the C-module was altered in reporter gene assays in the CbfA mutant compared to wild-type cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%